Design and characterization of calcium phosphate ceramic scaffolds for bone tissue engineering. Issue 1 (January 2016) - Denry, Isabelle; Kuhn, Liisa T.
Abstract: Objectives: Our goal is to review design strategies for the fabrication of calcium phosphate ceramic scaffolds (CPS), in light of their transient role in bone tissue engineering and associated requirements for effective bone regeneration. Methods: We examine the various design options available to meet mechanical and biological requirements of CPS and later focus on the importance of proper characterization of CPS in terms of architecture, mechanical properties and time-sensitive properties such as biodegradability. Finally, relationships between in vitro versus in vivo testing are addressed, with an attempt to highlight reliable performance predictors. Results: A combinatory design strategy should be used with CPS, taking into consideration 3D architecture, adequate surface chemistry and topography, all of which are needed to promote bone formation. CPS represent the media of choice for delivery of osteogenic factors and anti-infectives. Non-osteoblast mediated mineral deposition can confound in vitro osteogenesis testing of CPS and therefore the expression of a variety of proteins or genes including collagen type I, bone sialoprotein and osteocalcin should be confirmed in addition to increased mineral content. Conclusions: CPS are a superior scaffold material for bone regeneration because they actively promote osteogenesis. Biodegradability of CPS via calcium and phosphate release represents a unique asset. Structural control of CPS at the macro, micro and nanoscale and their combination with cells and polymeric materials is likely to lead to significant developments in bone tissue engineering.